Modernism and time machines - Tung, M. Charles (Edinburgh critical studies in modernist culture., 2019)
Modernism and Time Machines places the fascination with time in canonical works of twentieth-century literature and art side-by-side with the rise of time-travel narratives and alternate histories in popular culture. Both modernism and this cardinal trope of science fiction produce a range of effects and insights that go beyond the exhilarations of simply sliding back and forth in history. Together the modernist time-obsession and the fantasy of moving in time help us to rethink the shapes of time, the consistency of timespace and the nature of history.